2011
DOI: 10.1007/s12325-011-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitors and Lipids: Systematic Review and Meta-Analysis

Abstract: This meta-analysis suggests a possible beneficial effect of DPP-4 inhibitors on cholesterol, which, although small, could contribute to the reduction of cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 36 publications
9
128
3
3
Order By: Relevance
“…Although the number of trials of appropriate size and duration was high (n = 53), only a small fraction of those (n = 17) reported data on endpoint total, HDL and LDL cholesterol and TG levels. The difference in means for endpoint versus baseline total cholesterol in patients on DPP-4 inhibitor treatment was significantly higher in comparison with controls, meaning that treatment with DPP-4 inhibitors is associated with a significant reduction in total cholesterol (-0.18 (-0.29; -0.06) mmol/l (-7.0 (-11.2; -2.50) mg/dl); p = 0.002) [53].…”
Section: Sitagliptin and Lipid Profilementioning
confidence: 95%
“…Although the number of trials of appropriate size and duration was high (n = 53), only a small fraction of those (n = 17) reported data on endpoint total, HDL and LDL cholesterol and TG levels. The difference in means for endpoint versus baseline total cholesterol in patients on DPP-4 inhibitor treatment was significantly higher in comparison with controls, meaning that treatment with DPP-4 inhibitors is associated with a significant reduction in total cholesterol (-0.18 (-0.29; -0.06) mmol/l (-7.0 (-11.2; -2.50) mg/dl); p = 0.002) [53].…”
Section: Sitagliptin and Lipid Profilementioning
confidence: 95%
“…Meta-analyses showed lipid-lowering effects of several DPP4 inhibitors [28,29]. Aoki et al, evaluated the effect of anagliptin on serum lipid profiles, including cholesterol synthesis and absorption markers, in Japanese patients with type 2 diabetes.…”
Section: Dpp4 Inhibitors In the Management Of Hyperlipidemiamentioning
confidence: 99%
“…When added to previously taken antidiabetic agents, sitagliptin after 2 years of therapy reduced body weight and insulin resistance and improved lipid profile (reduction in total and LDL cholesterol, lowering of triglycerides and augmentation in HDL cholesterol) 80 . A meta-analysis suggested a possible beneficial effect of DPP-4 inhibitors on cholesterol, which, although small, could contribute to the reduction of CV risk 81 . In a recent meta-analysis of 70 trials with DPP-4inhibitors, a significant reduction in total cholesterol was observed (-0.28; 95% CI −0.46 to −0.10 mmol/l), with no significant changes in HDL cholesterol (-0.02; 95% CI −0.04 to +0.01 mmol/l) 66 .…”
Section: Lipid Profilementioning
confidence: 99%
“…Impaired insulin secretion Increased (glucose-dependent) insulin secretion 39 Increased glucagon levels Decreased (glucose-dependent) glucagon levels 39 Increased hepatic glucose production Decreased hepatic glucose production 39 Hyperglycemia Reduction in fasting and postprandial glycemia 50,51 Reduction in HbA1c 21,42 Body weight excess Weight neutrality (or small reduction) 21,27 Elevated blood pressure Modest reduction or no change in blood pressure 62,64,67 Dyslipidemia Reduction in postprandial lipemia 74,76,77,79 Mild improvement in fasting lipid profile 81 Silent inflammation Reduction in inflammatory markers (hs-CRP, IL-6, IL-18) 85,86 Oxidative stress Reduction in nitrotyrosine 53,86 Endothelial dysfunction Improved flow-mediated dilation 78,93,94 Platelet hyperactivity Reduction of platelet aggregation 99 …”
Section: Abnormalities In T2dm Favorable Effects Of Dpp-4 Inhibitorsmentioning
confidence: 99%